Elite Athletes’ In-event Competitive Anxiety Responses and Psychological Skills Usage under Differing Conditions - Hagan, John E.; Pollmann, Dietmar; Schack, Thomas (Frontiers in Psychology, 2017)
Even though the assessment of competitive anxiety responses (intensity, interpretation, and frequency) using the time-to-event paradigm has gained much attention, literature on the account of these same experiences in-event and their corresponding psychological skills adopted under differing conditions is limited. This is a follow up investigation to establish the extent to which associated anxiety responses are stable or dynamic and whether this pattern could be related to reported psychological skills under low or high stressful conditions across gender. Twenty-three high level (N= 13 males and 10 females) Ghanaian Table Tennis players provided data through completion of modified versions of Competitive State Anxiety Inventory-2 (CSAI-2), incorporated with directional and frequency of intrusion scales and the Test of Performance Strategies (TOPS) inventory during breaks within competitive fixtures. MANCOVAs (gender x stress condition) with follow-up analyses revealed no significant interactions and no main effect for gender but significant main effects were realized for all anxiety dimensions and psychological skills for only the second factor. Specifically, the intensity and frequency of cognitive and somatic state anxiety symptoms increased and were interpreted as debilitative under the high stress condition, although self-confidence and other array of psychological skills were highly displayed under the same stressful condition. Findings highlight the dynamic characteristics of in-event associated anxiety responses and ineffectiveness of deployed psychological skills regardless of gender. These perhaps show the exceptionality of affective experiences in an African setting, suggesting a culturally diversified approach to psychological skills application, if desirable effects are to be attained.